The Coronavirus as a Changemaker: Opportunities to Advance American Maternal Care in the Wake of the Pandemic - Anderson-Seller, Rachel (Columbia Journal of Gender and Law, 2022)
Birthing people in the United States pay more than citizens of other high-income countries and receive lower quality care, most of which is provided by physicians in hospital settings. Legal restrictions on midwives—the result of two centuries of pervasive sexist, racist, and anti-immigrant campaigns—prevent birthing people from making meaningful choices about their preferred birthing location and attendant, even though hospital births carry risks of their own. Policymakers may be hesitant to amend legislation and regulations due to a misperception that community birth is unsafe and that those who choose it are irresponsible. However, the COVID-19 pandemic presents an opportunity for change. In an effort to avoid hospitals, which are overwhelmed with COVID-19 patients and have enacted strict limits on support personnel during labor, birthing women are increasingly turning to community birth. Midwives and their clients can capitalize on this increased demand by advocating for an updated maternal care system.